PENGAWASAN TERHADAP PERATURAN KEPALA DAERAH - E. Prajwalita Widiati; Haidar Adam (Universitas Airlangga, 2012)
Decentralisation puts weigh in the dynamic of local government. As consequences of decentralization, local governments are entitled to enact local regulation in order to serve public services in the daily basis. Local regulation as the product of the Mayor of course does not stand alone. It is part of national legislative system which lay at the low tier of the hierarchy of laws. It should be work effectively and harmoniously with the system. By analyzing the nature of decentralization and the function of local legislation, it is essential to establish a good review mechanism for this legislative product. Different mechanism results in different consequences to the regulation. This article has analysed three mechanisms both preventive and represive; executive review which is done by the Governor and National Government; judicial review which is done by the Court and even political review which is exercised by the local representatives who act as balancing power to the local executive.Keywords: Peraturan Kepala Daerah, Executive Review, Judicial Review, Political Review